2020
DOI: 10.3390/cancers12020321
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Ubiquitin Ligase MEX3A Affects Glioblastoma Tumorigenesis by Inducing Ubiquitylation and Degradation of RIG-I

Abstract: Glioblastoma multiforme (GB) is the most malignant primary brain tumor in humans, with an overall survival of approximatively 15 months. The molecular heterogeneity of GB, as well as its rapid progression, invasiveness and the occurrence of drug-resistant cancer stem cells, limits the efficacy of the current treatments. In order to develop an innovative therapeutic strategy, it is mandatory to identify and characterize new molecular players responsible for the GB malignant phenotype. In this study, the RNA-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
(93 reference statements)
1
47
0
Order By: Relevance
“…In the process of cancer, RBP regulates the expression of many important genes post-transcriptionally by altering its encoded mRNA. Previous studies have shown that Mex3a regulates CDX2 in human colon cancer and promoted proliferation in gastric cancer and glioblastoma 2,4,18 . Here, for the first time, we identified that Mex3a was upregulated in human LUAD and high Mex3a expression correlated with positive lymph node metastasis, and advanced TNM stage, suggesting that Mex3a can be a strong predictor for LUAD metastasis and prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…In the process of cancer, RBP regulates the expression of many important genes post-transcriptionally by altering its encoded mRNA. Previous studies have shown that Mex3a regulates CDX2 in human colon cancer and promoted proliferation in gastric cancer and glioblastoma 2,4,18 . Here, for the first time, we identified that Mex3a was upregulated in human LUAD and high Mex3a expression correlated with positive lymph node metastasis, and advanced TNM stage, suggesting that Mex3a can be a strong predictor for LUAD metastasis and prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Mex3A appears crucial for the maintenance of the slowly cycling subpopulation of lgr5+ gut stem cells (Chatterji and Rustgi, 2018), and lgr5 absence in Mex3A −/− mice leads to growth retardation, postnatal mortality, and severe impairment of intestinal crypt development (Pereira et al, 2020). Recent data showed that MEX3A is up-regulated in glioblastoma specimens (Bufalieri et al, 2020). In glioblastoma cells, MEX3A interacts with the tumor suppressor RIG-I inducing its ubiquitinylation and the proteasome-dependent degradation, supporting tumor growth (Bufalieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data showed that MEX3A is up-regulated in glioblastoma specimens (Bufalieri et al, 2020). In glioblastoma cells, MEX3A interacts with the tumor suppressor RIG-I inducing its ubiquitinylation and the proteasome-dependent degradation, supporting tumor growth (Bufalieri et al, 2020). Although MEX3A has a key role in gastrointestinal homeostasis and tumor progression, its putative role in neural context is not yet defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations